Dingo Optimizer Plus Black Widow Optimization-Based Optimal Design of Multiband U-Slot Microstrip Patch Antenna - S. S., Ajitha (Cybernetics and systems, 2025)
Currently, for high-performance appliances the easiness of installation, weight, size, and cost are major constraints. Spacecraft, aircraft, missile, and satellite appliances require lower profile antennas, and U-slot MPA can be well fitted for such appliances because of its wide-band nature. MPA integrating U-shape slots are renowned for including comparatively larger bandwidth impedance (around 30%). This article aims to develop an optimized U-slot MPA design, where the antenna measurements such as patch height or board thickness, patch length, patch width, and feed diameter are optimally tuned by a new hybrid optimization model. As the concepts of Dingo Optimization and Black Widow Optimization are combined, the adopted algorithm is called Black Widow in Dingo Model with Logistic Chaotic Map. The priority of the introduced scheme is examined via the assessment over existing models by varying the frequency ranges, and cost analysis is also done for varied iterations.